Sanitization of potato varieties from the VIR collection against viruses - E. S. Bespalova; M. M. Agakhanov; S. B. Arkhimandritova; M. V. Erastenkova; Yu. V. Uhatova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. VIR’s potato collection is one of the oldest and richest; however, it is constantly exposed to viruses that negatively affect useful agronomic properties of tubers. Close monitoring of the phytosanitary state of potato accessions helps to select the most effective method of therapy for subsequent healing of infected plants and obtaining high-quality planting material.Materials and methods. The research was aimed at improving the health of 18 varieties of Solanum tuberosum L. from the VIR collection. Testing for the presence of viruses was based on the ICA and RTPCR techniques, and the consequent healing was performed using the methods of meristem culture and cryotherapy.Results and conclusions. During the field test of potato plants, PVX, PVS and PVA were found to be the most common viruses. PSTVd was completely absent in all tested accessions. The effectiveness of in vitro healing of potato plants from viruses was assesses using meristem culture. The percentage of healed plants was 0% for PVS, 0% for PVX, 33.4% for PVA, 50% for PLRV, 72.3% for PVY, and 83.4% for PVM. Healing with meristem culture was shown to be the most effective against PVY and PVM. While assessing the effectiveness of post-cryogenic restoration of potato microplants, the level of post-cryogenic regeneration of the shoot tips in potato microplants was determined at 22.3% on average for a sample. The minimum was observed in k-16762 ‘Sagita N’ (5%), and the maximum in k-1378 ‘Marta’ (41.7%). Analysis of the effectiveness of potato recovery from viruses by in vitro cryotherapy showed that the percentage of recovered plants was 100% for PVY, 100% for PVA, 88.9% for PVM, 77.8% for PVS, 44.4% for PVX. Thus, the techniques of apical meristem culture and cryotherapy proved to be effective against PVY, PVA and PVM viruses. However, in the case of multiple infections, it is necessary to combine elements of different healing protocols to increase the effectiveness of the healing procedure.